EXAMINATION FRAUD: A BANE OF THE ACHIEVEMENT MILLENNIUM DEVELOPMENT GOALS IN NIGERIA - A., Ibitoye S. (Sokoto Educational Review, 2020)
Worrisome is the unprecedented examination fraud pervading schools and various institutions of higher learning in Nigeria. While some examinees are vigorously preparing for examinations, others are busy strategizing to carry out examination fraud. This paper identified the varieties and facilitators of examination fraud in Nigeria vis-a-vis: parent/guardian, community, examination officials, institutional, and student-based examination fraud. It also brings out the implication of examination fraud for the achievement of the Millennium Development Goals (MDGs) in Nigeria. It suggested that less emphasis be placed on paper qualification in Nigeria. Stakeholders should vehemently enforce laws on examination malpractices, and thorough supervision of pedagogy should be done in both private and public schools to ensure that the teachers teach, and students learn genuinely.